Growth in the Rat's Brown Fat of a Hodgkin's-Like Transplantable Reticulo-Endothelial Tumour - Kinns, A. M. (1970)
A transplantable reticulo-endothelial (RE) tumour, originally derived from a tumour induced in rats by long term injections of trypan blue, shows metastatic spread to brown fat in the later stages of its growth. Growth in brown fat, in different anatomical sites, is dependent upon the route of initial cell inoculation. A hypothesis is put forward to explain this dependence.